2022
DOI: 10.1016/j.rcsop.2022.100104
|View full text |Cite
|
Sign up to set email alerts
|

“I'm at breaking point”; Exploring pharmacists' resilience, coping and burnout during the COVID-19 pandemic

Abstract: Background There is a lack of evidence on how the multimodal dynamic process of resilience has impacted personal adaptation of frontline healthcare professionals, working under extreme pressure during the COVID-19 global pandemic. Objectives To explore resilience, burnout and wellbeing for UK pharmacists in patient-facing roles, including individual and organisational factors that align to the ABC-X theoretical model of the dynamic process of resilience. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Stress has long been recognised as a key factor in patient safety events, and the increased levels of stress and burnout experienced by frontline healthcare staff during the pandemic are well documented. 25 , 26 A recent survey study by this research group found that 39% of pharmacists and 35% of GPs surveyed reported an increase in medication safety incidents during the pandemic. 13 Findings from this study suggest that for pharmacists, workflow changes and stress may have been potential contributory factors to this increase in incidents perceived by our participants.…”
Section: Discussionmentioning
confidence: 98%
“…Stress has long been recognised as a key factor in patient safety events, and the increased levels of stress and burnout experienced by frontline healthcare staff during the pandemic are well documented. 25 , 26 A recent survey study by this research group found that 39% of pharmacists and 35% of GPs surveyed reported an increase in medication safety incidents during the pandemic. 13 Findings from this study suggest that for pharmacists, workflow changes and stress may have been potential contributory factors to this increase in incidents perceived by our participants.…”
Section: Discussionmentioning
confidence: 98%
“…This domain may become a larger area of concern in the future, as risk of healthcare professional burnout appears to be increasing with the COVID-19 pandemic. 71 , 72 , 73 …”
Section: Discussionmentioning
confidence: 99%
“…A UK‐wide survey showed that COVID‐19 had a significant negative impact on local ASP activities that included auditing antimicrobials, quality improvement initiatives, education, ASP meetings, and multidisciplinary ward rounds. 41 One UK pharmacy survey classified respondents as high‐risk within the burnout scale and several pharmacists stated “I'm at a breaking point.” 42 Resilience and persistence led to new innovation during COVID‐19 that broadly falls into four main categories: (i) digitization, (ii) workforce changes, (iii) service integration, and (iv) person‐centered care. 43…”
Section: Resiliency Of Asps During the C...mentioning
confidence: 99%
“…41 One UK pharmacy survey classified respondents as high-risk within the burnout scale and several pharmacists stated "I'm at a breaking point." 42 Resilience and persistence led to new innovation during COVID-19 that broadly falls into four main categories: (i) digitization, (ii) workforce changes, (iii) service integration, and (iv) person-centered care. 43 Although competing priorities to deal with the pandemic have led to reduced focus on global strategies to tackle ASP, there have been…”
Section: United Kingdommentioning
confidence: 99%